Symposium 4: Policy networks, database pedagogies, and the new spaces of algorithmic governance in education - Williamson, Ben (Proceedings of the International Conference on Networked Learning, 2014)
Educational governance in the UK is increasingly being performed through cross-sectoral ‘policy networks’ and emerging forms of ‘network governance’ that signify a shift in political practices from centralized state government to a wider system of public, private and third sector interdependencies. This involves two shifts in the ‘governable spaces’ of educational policy: 1) a shift in the space of governance from central government to decentralized delivery based on a model or a ‘diagram’ of governance through networking and database architectures; and 2) a related shift in the space of educational governing practices from a focus on the national space of the education system to the mind and body of the individual as a ‘lifelong learner’ and a potential future person-in-the-making. This respatialization of educational governance entails moving from a focus on the ‘governable space’ of the education system, part of the public sector, to ‘governing through pedagogy’ in order to sculpt and mould the individual learner. The paper examines the participation of a particular policy network of third sector organizations in educational governance. Its approach to both educational governance and governing through pedagogy has as its objective the formation of ‘lifelong learners’ for a ‘pedagogized future’ which is to be interwoven with the algorithmic forms of the network and the database. In outline, the paper examines how third sector organizations aim to make education thinkable and intelligible through discourses and images that are based on the algorithmic forms of the network and database architectures. This is continuous with what has been termed in political science as ‘digital governance’ or ‘algorithmic governance.’ Digital governance operates through an ‘intelligent centre/decentralized delivery’ model which depends on the mobilization of a combination of networked communication technologies and database-driven information processing technologies. Then the paper examines how related new governing practices have been mobilized which seek to act directly through network and database technologies upon the thoughts, feelings, conduct and action of individuals. In particular these include social networking sites and other social media applications, and database-led ‘learning analytics’ and ‘adaptive software,’ which depend on complex algorithmic data analysis processes, as new forms of governing through pedagogy. Through these tactics, third sector organizations are seeking to reconfigure educational governance through decentralized networks and database architectures, and to reactivate individuals as ‘lifelong learners’, ‘mobile bodies’ and potential future persons-in-the-making through network-based and database-driven pedagogies.